2020
DOI: 10.1007/s10457-020-00494-6
|View full text |Cite
|
Sign up to set email alerts
|

Over-yielding in temperate silvopastures: a meta-analysis

Abstract: Over-yielding in an intercropping system occurs when the productivity of the intercrop exceeds the overall productivity of the systems managed in segregation. The objective of this systematic review was to calculate the over-yielding of silvopastures compared to open pastures and forests, timber plantations, or orchards managed separately. A literature search was completed for comparisons of the productivity of these practices in temperate regions. Data collected from these studies included mean yields of timb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 77 publications
0
18
1
Order By: Relevance
“…Silvopastoral systems produce a number of positive outcomes when compared with open pastures, including production benefits [e.g. land productivity (Pent 2020a); animal welfare (Broom et al 2013)], environmental benefits [e.g., increased biodiversity (Mosquera-Losada et al 2009)] and climatic benefits (e.g. carbon sequestration (Lorenz and Lal 2014); methane emissions reduction (Thornton and Herrero 2010)].…”
Section: Positive Outcomes Of Silvopastoral Systemsmentioning
confidence: 99%
“…Silvopastoral systems produce a number of positive outcomes when compared with open pastures, including production benefits [e.g. land productivity (Pent 2020a); animal welfare (Broom et al 2013)], environmental benefits [e.g., increased biodiversity (Mosquera-Losada et al 2009)] and climatic benefits (e.g. carbon sequestration (Lorenz and Lal 2014); methane emissions reduction (Thornton and Herrero 2010)].…”
Section: Positive Outcomes Of Silvopastoral Systemsmentioning
confidence: 99%
“…This system uses the resources more efficiently because different components compete at different space and time (Jose & Dollinger, 2019; Pent, 2020). As deep root systems of trees bind the soil, they reduce soil erosion and extract moisture from the deeper strata of the soil profile (Ghosh et al, 2020; Kumar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given the integrative effect of alley cropping, windbreaks and shelterbelts, scattered trees in pastures, and intensive management and rotational grazing, the spatial and temporal heterogeneity of silvopastoral system can maximize resource use e ciency (Cubbage et al 2012;Jose et al 2019). Numerous studies have shown that silvopastoral systems have multiple ecosystem service functions such as microclimate regulation (Karki and Goodman, 2013;Pezzopane et al, 2015), nutrient promotion (Barros et al, 2018;Lira et al, 2020), soil conservation (Bosi et al, 2020;De Abreu et al, 2020;Gyenge et al, 2002), productivity promotion (Pent, 2020;Sun et al, 2021) and biodiversity conservation (Roehrig et al, 2020;Mupepele et al, 2021). Meanwhile, the complementary rooting system in the silvopastoral system can make more e cient use of water (Pollock et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Which indicate that construction of silvopastoral system is bene cial for restoring soil physical quality of degraded pastures (Polania-Hincapie et al 2021). While neutral and negative interactions have been also reported for forages and trees will compete directly for available resource (Gyenge et al 2002;Pent, 2020). For example, soil water contents at deeper soil layers were decreased by introduced fodder crop in semiarid Loess Plateau (Ling et al, 2020); some studies have also shown noneffect or even a signi cant decrease in soil nutrient content after the construction of silvopastoral system (Qin et Under silvopastoral systems, naturally available resources (such as soil water and nutrients) have to be used e ciently to avoid competition among vegetation layers and maintain productions (Lopez-Diaz et al 2020).…”
Section: Introductionmentioning
confidence: 99%